"My Soul Is A Witness" Reimagining African American Women's Spirituality and the Black Female Body in African American Literature - Henderson, Carol (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This special collection assembles some of the most pre-eminent scholars in the field in African, African American, and American Studies to explore the ways writers reclaim the Black female body in African American literature using the theoretical, social, cultural, and religious frameworks of spirituality and religion. Central to these discussions is Black women's agency within these realms-their uncanny ability to invent and reinvent themselves within individual and communal spaces that frame them as both outsider and insider, unworthy and worthy, deviant and sacred, excess and minimal. Scholars have sought to discuss these tensions, acknowledged and affirmed in prose, poetry, music, essays, speeches, written plays, or short stories. Forgiveness, healing, redemption, and reclamation provide entry into these vibrant explorations of self-discovery, passion, and self-creation that interrogate traditional views of what is spiritual and what is religious. Discussed writers include Toni Morrison, Phillis Wheatley, James Baldwin, Tina McElroy Ansa, Toni Cade Bambara, and Thomas Dorsey.